A Study on Vitamin D3 in Pregnant Women and a Discussion of the Role of Some Other Parameters - Kazem, Abbas Fadel; Naji, Fatima Abdullrazaq; salman, Asawer rida; Turki, Zahraa Sameir (Journal of Science in Medicine and Life, 2024)
The relationship between low levels of vitamin D and various unfavorable pregnancy outcomes has been the subject of extensive research in the last several years. The only source of vitamin D for the fetus is the pregnant lady. Oily fish, fortified dairy products, and dietary supplements are the primary sources of vitamin D for expectant moms.. A increased risk of issues during a late-term pregnancy as well as some adverse consequences for the newborn have been associated with pregnancy-related vitamin D insufficiency. While there is variation in the published research results regarding gestational diabetes mellitus and preeclampsia, multiple large trials have suggested that taking supplements of vitamin D during pregnancy could reduce the likelihood of both diseases. Additionally, studies point to a potential link between elevated risk of preterm test results and decreased vitamin D concentrations ours.We evaluate the literature The contributing factors to the prevalence of vitamin D deficiency during pregnancy that contribute to it, and potential issues that may arise from it in our manuscript.